The Role of Khusamuddin Al-Akhsikati’s Scientific Heritage in Islamic Culture - Komiljanovna, Nishanova Dildora (International Journal of Psychosocial Rehabilitation, 2020)
All areas of Islamic science, particularly the Hanafi jurisprudence, were developed in Central Asia, and several works were written in Usul of al-fiqh and Furu al-fiqh. One of such scientific sources is the work of “Muntakhab al-Khusami” by Khusamuddin al-Akhsikati. It is important to study and research this work, which is popular among method scholars.